Water Temperature Effect on Hardness and Flexural Strength of (PMMA/TiO2 NPs) for Dental Applications - Zaynab N.Rahseed Alraziqi (مجلة بغداد للعلوم)
PMMA (Poly methyl methacrylate) is considered one of the most commonly used materials in denture base fabrication due to its ideal properties. Although, a major problem with this resin is the frequent fractures due to heavy chewing forces which lead to early crack and fracture in clinical use. The addition of nanoparticles as filler performed in this study to enhance its selected mechanical properties. The Nano-additive effect investigated in normal circumstances and under a different temperature during water exposure. First, tests applied on the prepared samples at room temperature and then after exposure to water bath at (20, 40, 60) C° respectively. SEM, PSD, EDX were utilized for samples evaluation in this study. Flexural strength, shear stress, hardness value were evaluated for all samples, the tests applied periodically at (15, 30, 45) min. Interestingly, it is found that at the normal condition (NC) the cooperation of TiO2 NPs significantly improves the selected properties. The maximum increase is located at 4 wt % of TiO2 NPs addition. The results also showed that temperature increase accelerate the water permeability within all samples thus decrease the mechanical properties. Obviously, a better hardness value determined for the prepared nanocomposite comparing to the control group at the same test condition.